UPAYA MENGATASI MISKONSEPSI TENTANG RANTAI MAKANAN MENGGUNAKAN MEDIA ICT DI SD - Imeldasari Sutisna, - (2023)
Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan ICT terhadap miskonsepsi pada materi rantai makanan di kelas V SD Negeri 2 Sindangherang, Kecamatan Panumbangan, Kabupaten Ciamis sebagai kelas experiment, dan kelas V SD Negeri 2 Sindangherang, Kecamatan Panumbangan, Kabupaten Ciamis sebagai kelas control. Jenis penelitian ini adalah penelitian kuantitatif atau eksperimen dengan desain quasi experimental design. Populasi dan sampel pada penelitian ini adalah siswa kelas V SD Negeri 2 Sindangherang sebagai kelas eksperimen, dan siswa kelas V SD Negeri 1 Sindangherang sebagai kelas control. Instrument yang digunakan untuk mengumpulkan data adalah pretest, posttest, dokumentasi dan lembar observasi, wawancara. Teknik pengumpulan data dalam penelitian ini adalah observasi dan tes (pretest dan posttest). Setelah data dikumpulkan kemudian pengolahannya dilakukan dengan analisis statistik deskriptif dan analisis statistik inferensial berbantuan sistem SPSS versi 25. Berdasarkan hasil penelitian dan pembahasan yang telah dilakukan, dapat diambil kesimpulan bahwa penggunaan ICT memiliki pengaruh yang signifikan terhadap pemahaman konsep, mengurangi miskonsepsi dan pemahaman materi rantai makanan pada siswa Kelas V SDN 2 Sindangherang. Berdasarkan hasil penelitian dan pembahasan yang telah dilakukan, pada siswa Kelas V SDN 2 Sindangherang sebagai kelompok eksperimen menunjukkan peningkatan pemahaman konsep sebesar 47%, pengurangan miskonsepsi 3%, dan peningkatan pemahaman materi 50% yang diketahui melalui nilai pretest dan posttest. Berdasarkan Independent Samples Test dapat ditunjukkan bahwa pada setiap kategori miskonsepsi (M), paham konsep (P) dan jumlah skor masing-masing nilai Equal variances assumed Sig. (2-tailed) yaitu 0,000 (< 0,05) sehingga dapat disimpulkan bahwa terdapat pengaruh pembelajaran menggunakan media ICT untuk meningkatkan hasil belajar, pemahaman konsep, mengurangi miskonsepsi (M) peserta didik pada materi rantai makanan di kelas V SDN 2 Sindangherang; Dengan kata lain, terdapat pengaruh yang signifikan antara penggunaan media ICT pada siswa Kelas V SDN 2 Sindangherang di Kecamatan Panumbangan Kabupaten Ciamis. This study aims to determine the effect of using interactive learning videos on misconceptions in food chain material in class V SD Negeri 1 Sindangherang, Panumbangan District, Ciamis Regency as the control class, and class V SD Negeri 2 Sindangherang, Panumbangan District, Ciamis Regency as the experimental class. This type of research is quantitative or experimental research with a quasi-experimental design. The population and sample in this study were fifth grade students at SD Negeri 1 Sindangherang as the control class, and fifth grade students at SD Negeri 2 Sindangherang as the experimental class. The instruments used to collect data were pretest, posttest, documentation and observation sheets, interviews. Data collection techniques in this study were observation and tests (pretest and posttest). After the data is collected, the processing is carried out using descriptive statistical analysis and inferential statistical analysis assisted by the SPSS version 25 system. Based on the results of the research and discussion that has been carried out, it can be concluded that the use of ICT (Interactive Learning Videos) has a significant effect on learning outcomes in Natural Sciences in Class V students at SDN 2 Sindangherang and reduce misconceptions. Based on the results of the research and discussion that has been carried out, the Class V students at SDN 2 Sindangherang as the experimental group showed an increase in conceptual understanding of 47%, a reduction in misconceptions of 3%, and an increase in material understanding of 50% which was known through pretest and posttest scores. Based on the Independent Samples Test, it can be shown that in each category of misconceptions (M), understanding of concepts (P) and the total score for each Equal variances value is assumed to be Sig. (2-tailed) namely 0.000 (<0.05) so that it can be interpreted that there is an influence of learning using ICT media to improve learning outcomes, understanding concepts, reducing students' misconceptions (M) on food composition material in class V SDN 2 Sindangherang; In other words, there is a significant influence between the use of ICT media in Class V students at SDN 2 Sindangherang in Panumbangan District, Ciamis Regency. Descriptively, the student learning outcomes in the experimental group showed an average pretest score of 62.7, while in the control group the pretest average score was 51. After going through the learning process, the posttest average score in the experimental group increased to 83.69 , whereas in the control group the posttest average score was 74. In inferential analysis using the independent sample t-test formula, it was found that the t_count value of 2.403 exceeds the t_table value of 2.069, with a significance value (sig) of 0.025 <0.05. This indicates that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. In other words, there is a significant relationship between the use of Interactive Learning Videos (ICT) and learning outcomes in Natural Sciences with reduced misconceptions by Class V students at SDN 2 Sindangherang in Panumbangan District, Ciamis Regency.